ONLINE MIND MAPS AS ONE OF THE MEANS OF MASTERING FOREIGN LANGUAGE VOCABULARY: https://doi.org/10.5281/zenodo.17265474 - Vishnyakova , E.A. (International scientific and practical conference, 2025)
Structuring information is important when learning vocabulary in a foreign language. Using mind maps will help students navigate new vocabulary more easily. Online mind map platforms can make this task easier.